Empowering Women Entrepreneurs in Indonesia Through Effective Government Assistance Programs - Maulidiah, Nur; Agustina, Isna Fitria (Indonesian Journal of Cultural and Community Development, 2024)
Background: The economic recovery of Sidoarjo Regency post-pandemic hinges on effective assistance programs for Micro, Small, and Medium Enterprises (MSMEs), particularly women's business groups. Specific Background: This study investigates the efficacy of the Sidoarjo Regency Government’s assistance program for independent women’s business groups, with a focus on its impact on resilience and independence within this demographic. Knowledge Gap: Despite existing literature on government assistance programs, there is a lack of detailed evaluations regarding their effectiveness, specifically in the context of women's entrepreneurship in Sidoarjo. Aims: This research aims to assess the effectiveness of the assistance program through qualitative methods, including interviews, observations, and documentation. Results: Findings reveal that the program has been effective, particularly for the Teman Setia Kitchen business, measured against Sutrisno's (2010) indicators: program understanding, target accuracy, timeliness, goal achievement, and real change. While some discrepancies with Standard Operating Procedures (SOP) exist, the overall impact on groups like Dapur Teman Setia, Mawar Boga, and Agung Tersena has been positive. Novelty: This study contributes to the body of knowledge by highlighting specific indicators of program effectiveness and providing actionable insights for improving governmental support for women entrepreneurs. Implications: The research underscores the importance of effective government intervention in fostering women’s entrepreneurship and calls for improved targeting and timeliness in aid disbursement, which are essential for the sustainable development of MSMEs in Sidoarjo. Highlights: Effectiveness measured: Understanding, target accuracy, and timely assistance evaluated. Positive impact: Increased income and improved welfare for women entrepreneurs. Communication gaps: Need for better outreach and administrative processes identified. Keywords: women's empowerment, MSMEs, government assistance, program effectiveness, economic recovery